Vertical and Circumferential Localization of Esophageal Mucosal Breaks in Patients with Mild Reflux Esophagitis - Kinoshita, Yoshikazu; Okada, Mayumi; Okimoto, Eiko; Adachi, Kyoichi; Notsu, Takumi; Mishiro, Tomoko (Internal Medicine, 2019)
Objective Esophageal mucosal breaks are considered to occur circumferentially in locations with high exposure to acid. In the present study, we investigated the circumferential localization of esophageal mucosal breaks based on their distance from the esophagogastric junction. Methods The vertical and circumferential localization of 625 esophageal longitudinal mucosal breaks was examined in 398 patients with mild reflux esophagitis. Results The number of mucosal breaks in which the distal end was located 0-1 cm from the esophagogastric junction was 454, while those in which the distal end was located 1-2, 2-3, and >3 cm from the junction were 125, 28, and 18, respectively. There was a marked difference in the circumferential distribution among the groups defined by distance from that junction. Esophageal mucosal breaks whose distal end were located 0-1 cm from the esophagogastric junction were mainly found on the right anterior wall of the esophagus, while those located 1-2 cm from the junction were mainly found on the right wall, and those located 2-3 and >3 cm from the junction were mainly found on the posterior wall. Conclusion Esophageal mucosal breaks occurring relatively near the esophagogastric junction mainly exist on the right anterior wall, whereas those farther from that junction tend to exist on the posterior wall of the esophagus. The circumferential location of esophageal mucosa highly exposed to refluxed gastric contents changes based on the distance from the esophagogastric junction.